Coded Aperture Nuclear Scintigraphy: A Novel Small Animal Imaging Technique - Dawid Schellingerhout; Roberto Accorsi; Umar Mahmood; John Idoine; Richard C. Lanza; Ralph Weissleder (Molecular Imaging, 2002)
We introduce and demonstrate the utility of coded aperture (CA) nuclear scintigraphy for imaging small animals. CA imaging uses multiple pinholes in a carefully designed mask pattern, mounted on a conventional gamma camera. System performance was assessed using point sources and phantoms, while several animal experiments were performed to test the usefulness of the imaging system in vivo, with commonly used radiopharmaceuticals. The sensitivity of the CA system for 99m Tc was 4.2 × 10 3 cps/Bq (9400 cpm/μCi), compared to 4.4 × 10 4 cps/Bq (990 cpm/μCi) for a conventional collimator system. The system resolution was 1.7 mm, as compared to 4–6 mm for the conventional imaging system (using a high-sensitivity low-energy collimator). Animal imaging demonstrated artifact-free imaging with superior resolution and image quality compared to conventional collimator images in several mouse and rat models. We conclude that: (a) CA imaging is a useful nuclear imaging technique for small animal imaging. The advantage in signal-to-noise can be traded to achieve higher resolution, decreased dose or reduced imaging time. (b) CA imaging works best for images where activity is concentrated in small volumes; a low count outline may be better demonstrated using conventional collimator imaging. Thus, CA imaging should be viewed as a technique to complement rather than replace traditional nuclear imaging methods. (c) CA hardware and software can be readily adapted to existing gamma cameras, making their implementation a relatively inexpensive retrofit to most systems.